2019
DOI: 10.1037/pag0000372
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in referential production: A multiple-measures study.

Abstract: Contemporary research on aging has provided mixed evidence for whether older adults are less effective than younger adults at designing and delivering spoken utterances. However, most of these studies have focused on only specific aspects of this process. In addition, they tend to vary significantly in terms of the degree of complexity in their chosen stimuli or task. The present study compares younger and older adults’ performance using a referential production paradigm involving simple everyday objects. We v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
(146 reference statements)
2
9
0
Order By: Relevance
“…To what extent do studies of referential communication provide evidence for patterns of decline that have been suggested in the broader literature on aging? To date, the most relevant work has focused on language production (e.g., Bortfeld, Leon, Bloom, Schober, & Brennan, 2001;Healey & Grossman, 2016;Horton & Spieler, 2007;Hupet, Chantraine, & Nef, 1993;Kemper, Othick, Warren, Gubarchuk, & Gerhing 1996;Kemper, Vandepute, Rice, Cheung, & Gubarchuk, 1995;Long et al, 2018;Saryazdi, Bannon, & Chambers, 2019). Studies have shown that, whereas younger adults seem to readily tailor their referential expressions based on the knowledge state of their addressees, older adults exhibit little adaptation (e.g., Horton & Spieler, 2007;Kemper et al, 1995Kemper et al, , 1996.…”
Section: Aging and Referencementioning
confidence: 99%
“…To what extent do studies of referential communication provide evidence for patterns of decline that have been suggested in the broader literature on aging? To date, the most relevant work has focused on language production (e.g., Bortfeld, Leon, Bloom, Schober, & Brennan, 2001;Healey & Grossman, 2016;Horton & Spieler, 2007;Hupet, Chantraine, & Nef, 1993;Kemper, Othick, Warren, Gubarchuk, & Gerhing 1996;Kemper, Vandepute, Rice, Cheung, & Gubarchuk, 1995;Long et al, 2018;Saryazdi, Bannon, & Chambers, 2019). Studies have shown that, whereas younger adults seem to readily tailor their referential expressions based on the knowledge state of their addressees, older adults exhibit little adaptation (e.g., Horton & Spieler, 2007;Kemper et al, 1995Kemper et al, , 1996.…”
Section: Aging and Referencementioning
confidence: 99%
“…On the other hand, the ageing brain is capable of remarkable plasticity, which may make older adults (with a lifetime of language experience) better equipped to adopt effective production strategies based on available cognitive resources 37,38,39,40 . Recent work suggests that individual differences in response to ageing may account for divergent linguistic outcomes: While some older adults are indistinguishable from younger adults in perspective-taking 11 , fluency 41,42 , and ambiguity avoidance 43 , others display marked decline in the same areas 44,33,6 .…”
Section: Ageing and Cognitive Controlmentioning
confidence: 99%
“…On the other hand, the ageing brain is capable of remarkable plasticity, which may make older adults (with a lifetime of language experience) better equipped to adopt effective production strategies based on available cognitive resources [37][38][39][40] . Recent work suggests that individual differences in response to ageing may account for divergent linguistic outcomes: While some older adults are indistinguishable from younger adults in perspective-taking 11 , fluency 41,42 , and ambiguity avoidance 43 , others display marked decline in the same areas 6,33,44 .…”
mentioning
confidence: 99%